Students’ Perceptions of Chatgpt as A Speaking Partner in Tourism English Role-Play: Implications for Ai-Enhanced Language Learning - Dhimas Dwi Nugraha Hadistya (UPT P2M Politeknik Negeri Malang, 2025)
ABSTRACT This study examines the perceptions of 25 English for Tourism Industry students at the State Polytechnic of Malang on using ChatGPT as a speaking partner in tour guide role-plays. The research aimed to evaluate its effectiveness in improving fluency, vocabulary, and confidence, while noting challenges such as speech recognition errors, limited response variety, and technical issues. Data were gathered through Likert-scale questionnaires and open-ended responses and analyzed both quantitatively and qualitatively. The results showed that students valued ChatGPT for vocabulary enrichment and fluency practice, though it was seen as a complement rather than a substitute for human interaction. The study highlighted the potential of integrating AI into Tourism English curricula while calling for enhanced feedback and conversational realism.